Novel Filtering Power Divider With Wide Stopband Using Discriminating Coupling - Zhao, Xiao-Lan; Gao, Li; Zhang, Xiu Yin; Xu, Jin-Xu (IEEE microwave and wireless components letters, 2016)
A novel filtering power divider with wide stopband is presented in this letter. It utilizes four coupled quarter-wavelength resonators to obtain dual functions. Discriminating coupling is applied to the input and output feed lines and resonators, which not only to provide suitable coupling strength but also to suppress 3f 0 and 5f 0 (f 0 is the operating frequency). A resistor is connected at the two open-ends of the input feed line to obtain high isolation. Transmission zeros are generated near the passband edges, resulting in high selectivity. For demonstration, a power divider with filtering function as well as wide stopband is implemented. Good agreement between the prediction and measurement validates the proposed method.